Modelling Ediacaran metazoan–microbial reef growth. Issue 5 (26th December 2020) - Curtis, Andrew; Wood, Rachel; Bowyer, Frederick; Shore, Amy; Curtis‐Walcott, Alastair; Robertsson, Johan
Abstract: Throughout the Phanerozoic, sessile metazoans grew in close association with various microbial carbonates to form reefs. The first metazoans with calcareous hard‐parts appeared in the terminal Ediacaran, ca 550 million years ago, and these also commonly grew associated with microbial mats, thrombolites and stromatolites, to form the oldest known metazoan–microbial reefs. These hard‐parts also formed the first skeletal (bioclastic) carbonate sediments, which increased to dominate shallow marine carbonate sedimentary production during the Phanerozoic. Here the growth dynamics and sedimentary interactions between Ediacaran microbial–metazoan reefs and their bioclastic products are described based on reef complexes from the Nama Group, Namibia ( ca 547 Ma), and the first three‐dimensional numerical models are constructed to parametrize these dynamics. These reefs are observed to form large domal mounds and columns neighbouring locally high rates of bioclastic sediment accumulation, and commonly evolve to flat‐topped surfaces overlain by sediment. This model is parsimonious, embodying a single dynamic rule: metazoans attach to microbialite mounds which grow radially into free space shedding bioclasts in proportion to metazoan production . Models evolve mounds into columns due to spatial competition, and produce an oscillating interplay between mound expansion and smothering that results in an inter‐fingering of microbialite mound and detrital sediment. This dynamic is shown to be non‐linear in the proportion of bioclastic sediment produced. Smothering by bioclastic sediment is also demonstrated to both reduce the rate (by volume) of subsequent mound growth, and to overwhelm the growing mat surfaces of stromatolites: after a threshold is reached in the rate of bioclastic sediment deposition, sediment terminates all stromatolite growth. These models show that the general characteristics of field observations can be explained by a single dynamic rule, and that reef‐sourced bioclasts may make an important local contribution to Ediacaran to Cambrian microbial–metazoan reef dynamics – a contribution that remains important throughout the Phanerozoic.